PENGARUH DESENTRALISASI FISKAL, EFISIENSI DAN EFEKTIVITAS PENYERAPAN ANGGARAN TERHADAP AKUNTABILITAS PELAPORAN KEUANGAN PEMERINTAH DAERAH PROVINSI ACEH - Muraiya Muraiya; Nadirsyah Nadirsyah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This study aims to examine the influence of fiscal decentralization, efficiency and effectiveness of budget absorption on the accountability of local financial reporting in Aceh Province by using audit opinion by BPK RI as a proxy of accountability of local financial reporting. Audit opinion was collected from Inspection Report which contained data on the Internal Control System. The samples of this research are the districts/municipals in Aceh Province which amounted to 23 districts/municipals as the final samples. Data of fiscal decentralization, efficiency and effectiveness of budget absorption were collected by Budget Realization Report, then data were analyzed using logistic regression analysis. The results of this research show that (1) fiscal decentralization, efficiency and effectiveness of budget absorption simultaneously have influence on the accountability of local financial reporting in Aceh Province, (2) fiscal decentralization has influence on the accountability of local financial reporting in Aceh Province, (3) efficiency of budget absorption has no influence on the accountability of local financial reporting in Aceh Province, and (4) effectiveness of budget absorption has influence on the accountability of local financial reporting in Aceh Province.